(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data mining methods are used to derive valuable knowledge from raw data. The information gained is important and greatly impacts the decision-maker. Educational Data Mining (EDM) is a means of collecting useful information that could potentially affect an entity. Increasing the use of technology in education systems has contributed to the storing of vast amounts of student data, which makes it important to use EDM to enhance teaching and learning processes. Educational institutions are one of the most essential parts of our society and play a vital role in the growth and development of any country. Data Mining is an evolving methodology that can easily learn from historical data and use that information to predict future activity in areas of concern.